A Case of Severe Multisystem Inflammatory Syndrome in Children (MIS-C) Treated with Multiple Biologics - Beenish Zulfiqar; Hira Imran; Kathleen Collins (Case Reports in Rheumatology)
The COVID-19 virus has impacted global health on a wide scale, affecting humans of all ages and ethnicities. While most have mild upper respiratory viral symptoms, some have died due to severe pneumonia, acute respiratory distress syndrome (ARDS), or coagulopathies to mention a few. It has been postulated that the COVID-19 virus can initiate an autoinflammatory reaction in the body via multiple pathways of cytokine activation. The virus can cause delayed response after 4–8 weeks of acute infection, which resembles a cytokine storm or MAS (macrophage activation syndrome). This highly inflammatory syndrome, called MIS-C or multisystem inflammatory response syndrome, needs to be diagnosed and treated early to prevent multiorgan damage and mortality. There are widespread lab abnormalities including highly elevated acute phase reactants ferritin, D-Dimer, lactate dehydrogenase (LDH), creatinine kinase (CK), sedimentation rate (ESR), and C-reactive protein (CRP) as well as markers of cardiac damage including troponin and brain natriuretic peptide (BNP). The syndrome can present in unique ways from classic MIS-C with hypovolemic shock to Kawasaki disease-like presentation. We present a case of a 12-year-old boy who presented to Le Bonheur Children’s Hospital in Memphis with classic signs and symptoms of “severe” MIS-C requiring intubation, multiple pressors, ECMO, and renal replacement therapy. He was treated successfully with immunomodulating medicines including intravenous immune globulin (IVIG), steroids, interleukin-6 inhibitor, tumor necrosis factor-a inhibitor, interleukin-1 inhibitor, and Janus kinase inhibitor.